Estrategia TIC, para La resolución de problemas hacia el fortalecimiento del pensamiento lógico matemático - Macías Rojas, Mónica Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Rural education, an opportunity to explore different technologies that allow combining knowledge as a way of learning different from the paths of traditionalism; Mathematics, a versatile area that is based on logical thinking and problem solving, being part of the academic processes and the context of the students. The objective of this research is to develop logical thinking, for the resolution of mathematical problems through ICT, in the Roberto Franco Isaza Educational Institution, using online and offline ICT tools, applied in the mathematics classroom. This research is developed with tenth grade students, whose ages range between 15 and 20 years; qualitative methodology, where the information is established from the field diaries, semi-structured interview, empirical workshop and output.